Ocular changes in pregnancy - Garg, P; Aggarwal, P (Nepalese Journal of Ophthalmology, 2012)
Pregnancy is often associated with ocular changes which may be more commonly transient but occasionally, permanent. The ocular effects of pregnancy may be physiological or pathological or may be modifications of pre-existing conditions. Physiological changes include increased pigmentation around the cheeks, ptosis, changes in cornea and refractive status, decreased intraocular pressure. These usually resolve post partum. Pre-existing diseases such as Graves’ disease, Retinitis pigmentosa, Optic neuritis, should be monitored due to their remission or relapses in pregnancy. There may be worsening of Diabetic retinopathy, and Central serous chorio-retinopathy with increased risk of Retinal detachment. Conditions like Glaucoma and Non infectious uveal inflammatory disorders may even improve transiently. Pre-eclampsia and eclampsia could result in hypertensive retinopathy, exudative retinal detachment and cortical blindness. Neuro-ophthalmological disorders such as venous sinus thrombosis, benign intracranial hypertension, pituitary adenoma, meningioma and optic neuritis should be kept in mind as differential diagnosis in pregnant women presenting with visual acuity loss, visual field loss, persistent headaches or oculomotor palsies. Use of ophthalmic drugs can affect fetal health during pregnancy. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5867 NEPJOPH 2012; 4(1): 150-161